Rozważania nad dopuszczalnością pełnienia funkcji sołtysa przez duchownego Kościoła Katolickiego - Pańczyk, Filip (Studia Prawa Publicznego, 2021)
This article is an analysis of legal admissibility of performing the office of a village administrator by a catholic priest. Despite the fact that this theme has already been a subject of doctrine’s interest, this study distinguish itself from other studies because it is based on a case that took place in practice. That means, obviously, a choice of the Archbishop Sławoj Leszek Głódź for a village administrator of Piaski. Considerations are conducted from three perspectives – commonly applicable law, The Concordat itself and the canonic law. Comparative legal perspective provides a citation of relevant regulations existing in chosen countries. There are also introduced regulations referring to the status of a village administrator in Polish legal order. Conducted considerations allow to conclude that in spite of the fact that Polish commonly applicable law and the Concordat itself strongly emphasize the principle of autonomy and mutual independence of the state and churches and other religious unions, they do not provide for a prohibition of taking over public offices by priests. This case is differently regulated by the Code of Canon Law which directly forbids priests to execute offices connected with performing of public authority. Such offices should involve office of a village administrator, what determines the inadmissibility of performing the office of village administrator by catholic priest.